2019
DOI: 10.3354/esr00960
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and temporal patterns in the acoustic detection of sperm whales Physeter macrocephalus in the central and western North Pacific Ocean

Abstract: The easily identifiable, high-amplitude echolocation signals produced by sperm whales Physeter macrocephalus make the species ideal for long-term passive acoustic monitoring. Sperm whale signals were manually identified in the recordings from high-frequency acoustic recording packages monitoring 13 deep-water locations across the central and western North Pacific Ocean from 2005 to 2013, constituting the longest passive acoustic study of sperm whales to date. The species was detected at all of the sites, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 83 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…However, the possibility of significant physical or acoustic interactions during dawn and dusk should be explored further, and anthropogenic noise may still impact their daytime resting even when they are less acoustically active. Additionally, several species of odontocetes are active and detected at this site during all hours of day and night (e.g., Baumann-Pickering et al, 2014;Merkens et al, 2019), increasing the chances of acoustic overlap and masking for those species.…”
Section: Contributions Of Anthropogenic Signalsmentioning
confidence: 99%
“…However, the possibility of significant physical or acoustic interactions during dawn and dusk should be explored further, and anthropogenic noise may still impact their daytime resting even when they are less acoustically active. Additionally, several species of odontocetes are active and detected at this site during all hours of day and night (e.g., Baumann-Pickering et al, 2014;Merkens et al, 2019), increasing the chances of acoustic overlap and masking for those species.…”
Section: Contributions Of Anthropogenic Signalsmentioning
confidence: 99%
“…2) and oceanographic conditions affecting the position of the thermocline (Shabangu et al 2020c). Similarly, Merkens et al (2019) observed no single diel pattern across locations in the Pacific Ocean.…”
Section: Discussionmentioning
confidence: 88%
“…The stereophony of the sonobuoy allowed us to compute TDoAs tracks, enabling an efficient browse of long-term data for annotation of presence/absence as well as for estimating the number of simultaneous individuals. The Mediterranean sperm whale subpopulation had already been studied at very large geographical scales 41 43 , while other populations were monitored over long time period such as Gordon et al 44 (4 months), Ward et al 45 (42 days), Ackleh et al 46 (4 month over 7 years), Caruso et al 32 (9 months), Merkens et al 47 (15 cumulative years of recordings).…”
Section: Discussionmentioning
confidence: 99%